Renewable energy development towards sustainable development goals: a review of Thailand's and the Philippines’ laws and policies - Ghazali, Farahdilah; Abdul Shukor, Siti Fazilah; Karim, Ridoan (Universiti Sultan Zainal Abidin, 2024)
Background and Purpose: Renewable energy (RE) is vital for sustainable energy access and climate change mitigation. Despite rising energy demand, Thailand and the Philippines have made limited progress in integrating RE into their energy portfolios. Both countries have implemented policies and projects aligned with Target 7 of the Sustainable Development Goals (SDGs), which emphasizes affordable and sustainable energy for all. This study examines the effectiveness of legal and policy frameworks in overcoming barriers to RE development and supporting sustainable energy transitions. Methodology: A comprehensive library-research methodology was employed, incorporating statutory and conceptual approaches. Key legislations, such as Thailand’s National Energy Policy Act (1992) and the Philippines’ Renewable Energy Act (2008), were reviewed to evaluate their alignment with sustainability principles and SDG commitments. The analysis focused on identifying regulatory gaps, financial barriers, and governance challenges within the RE landscape. Findings: The findings indicate that, while RE presents significant potential for socioeconomic development and energy security, its growth is hindered by regulatory inefficiencies, financial constraints, and limited government support. Comprehensive legal frameworks and targeted incentives are essential to address these barriers and promote a transition to a sustainable energy mix. Contributions: This study contributes to the discourse on RE governance by highlighting the need for robust policies, financial incentives, and stakeholder collaboration. It provides insights for policymakers to enhance RE adoption and achieve sustainable development goals in Thailand and the Philippines.